A review of small incision lenticule extraction complications. Issue 4 (July 2018) - Krueger, Ronald R.; Meister, Caio S.
Abstract : Purpose of review: As a flapless procedure, SMILE brings benefits to refractive surgery, such as lower corneal biomechanical impact, less dry eye risk and less stromal bed exposure. However, the longer learning curve can be a risk factor for complications. This article aims to discuss SMILE complications and proposes a categorized analysis of occurrences, dividing into two groups: intraoperative and postoperative complications. Among intraoperative, we also suggest a subdivision between those related to the laser (lenticule construction), tissue separation (lenticule dissection) and tissue removal (lenticule extraction). Recent findings: The majority of SMILE complications are related to surgeon inexperience and reversible if precociously diagnosed and correctly managed. Intraoperative complications related to lenticule creation such as suction loss, opaque bubble layer and black spots, are correlated with later difficulties during lenticule dissection and removal, and may lead to unwanted situations, such as cap perforation, lenticule tear and cap-lenticule adhesion. Postoperative complications as dry eye, keratitis and ectasia should not be underestimated. Summary: Analyzing what has been reported as major or unique among the complications with SMILE, and dividing them into subgroups, we aim to help refractive surgeons in becoming familiar with the things that can go wrong during SMILE. Early recognition and correct management will be fundamental for optimizing the final visual result.